2008
DOI: 10.17221/2779-pse
|View full text |Cite
|
Sign up to set email alerts
|

Differences in phenolic content and antioxidant activity in yellow and purple-fleshed potatoes grown in the Czech Republic

Abstract: The aim of this study was to determine the total phenolic (TP) content and antioxidant activity (AA) in yellow (cvs. Impala, Karin, Dita, Saturna) and purple-fleshed (cvs. Valfi, Violette) potatoes grown in the Czech Republic in 2004 in four locations in precise field trials. TP content was determined by Folin-Ciocalteau assay and AA by DPPH assay both in freeze-dried tuber matter. Results showed a statistical significant difference in TP content and AA between yellow and purple-fleshed potatoes. Purple-fleshe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 17 publications
4
16
0
1
Order By: Relevance
“…Saturna, Agria and Asterix varieties showed the lowest TP content (4.18, 4.27 and 4.53 mg/g DM, respectively), which unlike other yellow-fleshed varieties in this set feature with a higher content of dry matter, farinaceous consistency of flesh and are suite for the production of fried food products. Conclusive effect of genotype on the contents of TP, which we found in the normal range of yellow-fleshed varieties in our experiments, corresponds to the results of other authors (Lachman et al 2008, André et al 2007, 2009b. contents were shown to be lower compared to Highland Burgundy Red and the other abovementioned varieties; the differences between them were non-significant.…”
Section: Field Trials At the Lípa Location 2004-2008supporting
confidence: 92%
See 1 more Smart Citation
“…Saturna, Agria and Asterix varieties showed the lowest TP content (4.18, 4.27 and 4.53 mg/g DM, respectively), which unlike other yellow-fleshed varieties in this set feature with a higher content of dry matter, farinaceous consistency of flesh and are suite for the production of fried food products. Conclusive effect of genotype on the contents of TP, which we found in the normal range of yellow-fleshed varieties in our experiments, corresponds to the results of other authors (Lachman et al 2008, André et al 2007, 2009b. contents were shown to be lower compared to Highland Burgundy Red and the other abovementioned varieties; the differences between them were non-significant.…”
Section: Field Trials At the Lípa Location 2004-2008supporting
confidence: 92%
“…The lowest TP content was determined in the Shetland Black variety (19.4 mg/g DM), which has purple flesh only in and around vascular bundles. Like in our case, Lachman et al (2008) and Rumbaboa et al (2009) also showed a significant difference in TP content between different varieties of purple-and red-fleshed tubers. Content of chlorogenic acid was investigated in an experiment in 2008 within the same group of eight varieties of coloured flesh as in the case of TP, which enabled to express the correlation relationship between the contents of TP and chlorogenic acid.…”
Section: Field Trials At the Lípa Location 2004-2008supporting
confidence: 87%
“…Equally important, some colourful foodstuff pulps such as yellow or purple fleshed sweet potatoes exhibit very good amount of phenols. In this case, Karin yellow flesh exhibited 3.44 and valfi purple flesh 4.81 mg GAE/g (Lachman et al, 2008). In addition, cactus pear fruits' pulp, Opuntia ficus-indica, has 0.892 for the purple colour and 0.698 mg GAE/g for the yellow one on fresh matter (Albano et al, 2015).…”
Section: Total Phenolsmentioning
confidence: 84%
“…Due to the revealed importance of orange, purple or yellow coloured foodstuffs, known as important sources of polyphenols (Lachman et al, 2008;Dantas et al, 2016), whilst we didn't come across of a paper on the drying temperature impact on Palmira palm pulp nutritional value, we assessed B. aethiopum mature fruits pulp nutritional quality under different drying temperatures. So, the hypothesis investigated in this paper was that the drying temperature can affect total phenols and flavonoids content, thus the antioxidant activity of Borassus aethiopum Mart ripe fruits' pulp.…”
Section: Introductionmentioning
confidence: 99%
“…For the determination of total phenols used the method described by Lachman [19]. Was defined, also the antioxidant capacity of the samples, and thus extract the oil capacity and reduce ABTS radical according to the spectrophotometric method [20].…”
Section: Antioxidant Activitymentioning
confidence: 99%